Talking Academic Writing: A Conversation Analysis of One-to-One Learning Development Tutorials - Caldwell, Elizabeth; Stapleford, Katharine; Tinker, Amanda (Journal of Academic Writing, 2018)
Within the Learning Development community there are few professional development opportunities or resources for new entrants to the profession, particularly with regard to conducting individual academic writing tutorials. The current study seeks to address this by analysing the talk of individual academic writing tutorials in order to better understand how tutorials are organised and conducted, how identities and relationships are established and how learning is developed. We analysed the audio recordings of one-to-one academic writing tutorials and used conversation analysis methodology to identify features of effective practice. The analysis revealed an overarching three-part sequential structure to the tutorials and identified several features of effective practice in the middle phase where advice-giving occurs. The key finding was that indirect and complex processes of highlighting problems and arriving at solutions are useful to develop learners’ skills and autonomy. The application of these insights has the potential to contribute to a more evidence-informed reflective community of Learning Development practitioners.